An effective and cost‐saving structured education program teaching dynamic glucose management strategies to a socio‐economically deprived cohort with type 1 diabetes in a VIRTUAL setting. Issue 7 (12th July 2022) - Pemberton, John S.; Barrett, Timothy G.; Dias, Renuka P.; Kershaw, Melanie; Krone, Ruth; Uday, Suma
Abstract: Objectives: Compare the clinical and cost‐effectiveness of an established face to face (F2F) structured education program to a new remote (VIRTUAL) program teaching dynamic glucose management (DynamicGM) to children and young people with type 1 diabetes (CYPD) using continuous glucose monitoring (CGM). To ascertain the most effective DynamicGM strategies predicting time in range (TIR) (3.9–10.0 mmol/L) and incorporating these into a user‐friendly teaching aid. Design and methods: Effectiveness of the F2F and VIRTUAL programs were ascertained by comparing the mean change (Δ) from baseline to 6 months in HbA1c, TIR and severe hypoglycemia. Delivery cost for the two programs were evaluated. Factors predicting TIR in the combined cohort were determined and incorporated into a user‐friendly infographic. Results: First 50 graduates per group were evaluated. The mean difference in Δ HbA1c, Δ TIR and Δ episodes of severe hypoglycemia between VIRTUAL and F2F groups were 1.16 ( p  = 0.47), 0.76 ( p  = 0.78) and −0.06 ( p  = 0.61) respectively. Delivery cost per 50 CYPD for VIRTUAL and F2F were $5752 and $7020, respectively. The strongest predictors of TIR ( n  = 100) were short bursts of exercise (10–40 min) to lower hyperglycemia ( p  < 0.001), using trend arrow adjustment tools ( p  < 0.001) and adjusting pre‐meal bolus timing based on trend arrows ( p  < 0.01). These strategies were translated into a GAME (Stop highs), SET (Stay in target), MATCH (Prevent lows) mnemonic. Conclusion: Teaching DynamicGM VIRTUALLY is just as effective as F2F delivery and cost saving. Short bursts of exercise and using CGM trend arrows to adjust insulin dose and timing improves TIR.